Strategic analysis of hardships and opportunities for developing urban tourism(Pilot study: shahr-e-kord) (تحقیقات کاربردی علوم جغرافیایی)
In recent decades, developing urban tourism as one of major economic activities in different countries has caused many managers and planners to consider increased quality of tourism experience and protecting interests of host communities to expand the activities of this industry, knowing potentials, existing problems, decision making and planning. To do so, strategic planning can be propounded as a response to difficulties occurred due to lack of appropriate planning in tourism. In core tourism like all other commercial activities, strategic tourism should be depicted. So, one of strategic planning models used to develop tourism particularly urban tourism is a traditional model called SWOT. Therefore, in present study, it has been endeavored of Shahr-e-kord located in Chaharmahal-e-Bakhtiari as well as to analyze difficulties and problems existing in respect of Shahr-e-kord tourism. His study is a descriptive-analytic one and was done using filed studies and data gathered through evidence and libraries, questionnaires (considering the attitude of 70 officials and tourists) and Internet. Then, data was analyzed using excel software and strategic model of SWOT. Results suggested that due to having high capacities for tourism, Shahr-e-kord suffers from lack of enough infrastructure problems. On the other hand, it encompasses opportunities for educated young people to be employed and for investing. Some of major solutions to develop tourism are to increase advertisement, provide welfare and accommodation facilities, attract investment and be protected by government.